SOLAR POWER TREE: A SUSTAINABLE INNOVATION IN ENERGY HARVESTING (CAHIERS MAGELLANES-NS, 2024)
Abstract: The Solar Power Tree is a cutting-edge method of capturing solar energy and gives a possible response to the increasing global demand for renewable energy sources. The Solar Power Tree's concept and advantages are examined in this abstract. It consists of a central pole that resembles the trunk of a tree with several solar panels organized in a radial pattern, simulating the canopy of a tree. This design uses the least amount of land possible while maximizing energy capture, making it the best option for confined urban spaces. The Solar Power Tree has a number of benefits, including improved energy efficiency, a smaller environmental impact, and adaptation to different environmental factors. Its sophisticated design is also aesthetically pleasing and blends in well with urban environments. Additionally, because of its scalability and modular design, it is appropriate for both small-scale residential.